Maximum power output performance modeling of solar photovoltaic modules - A. Hadj Arab; B. Taghezouit; K. Abdeladim; S. Semaoui; A. Razagui; A. Gherbi; S. Boulahchiche; I. Hadj Mahammed (Energy Reports, 2020)
The aim of this work is to present the results of maximum power performance measurements of PV modules of the first grid-connected PV system installed at Centre de Développement des Energies Renouvelables (CDER), working since June 2004. The analysis has shown that all the PV modules are producing power, but less than rated value. In our case, two mathematical models have been used in order to determine the maximum power output (Pmax) delivered by the PV module as function of the solar irradiance intensity and the PV-module temperature. Comparison have been made for the two models. Note that PVWATTS model is simpler than the analytical five-parameter model.
Keywords: 330; Maximum power; Performance; Photovoltaic module; Temperature correction